An emulsified starch and a method for preparing the same
Patent Information
- Application Number
- CN202611157065.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-30
AI Technical Summary
多年来,美国、欧洲、日本等国的科学家对该产品的制备方法和应用技术进行了改进,在国内外辛烯基琥珀酸淀粉酯已投入工业化生产,产品市场前景看好,但在配料表中需标注为辛烯基琥珀酸淀粉钠,属于食品添加剂范畴,在很多领域会被限定使用
[0032]本发明的有益效果是:本发明不加入食品添加剂也能制备得到乳化淀粉,所得产品在出售时无需带有食品添加剂标识,生产过程绿色环保,无需排放高盐废水,该乳化淀粉具有良好的乳化稳定性,能广泛应用于食品领域。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to an emulsified starch and its preparation method, belonging to the technical field of edible modified starch preparation. Background Technology
[0002] Emulsified starch, commonly known as octenyl succinate starch ester, is obtained through a chemical synthesis reaction between octenyl succinic anhydride and starch, forming ester bonds between molecules. It is widely used in the food industry as an emulsifying, protective, and stabilizing agent, typically existing in the form of sodium octenyl succinate starch, a highly safe emulsifying and thickening agent. Over the years, scientists in the United States, Europe, Japan, and other countries have improved the preparation methods and application technologies of this product. Octenyl succinate starch ester has been put into industrial production both domestically and internationally, and the market prospects are promising. However, it must be listed as sodium octenyl succinate starch in the ingredient list, falling under the category of food additives, and its use is restricted in many areas. Furthermore, the conventional wet production process of sodium octenyl succinate starch involves suspending starch in water for a chemical reaction, generating large amounts of wastewater and placing significant environmental pressure on treatment. In recent years, modified starch companies have begun to focus on green processing technologies that reduce chemical use and wastewater discharge.
[0003] Oil starch is basically obtained by thoroughly mixing oil and starch raw materials. The industry has developed products that can be used in fields such as frying coating powder and bread premix powder. When used in batter, it can significantly improve the adhesion of the batter.
[0004] To date, sodium octenyl succinate starch has been widely used due to its combined thickening and emulsifying stabilizing properties. However, with the improvement of living standards, people are paying more and more attention to food additives on labels. Under these circumstances, there is an urgent need for an efficient, green and environmentally friendly manufacturing method to obtain starch with high emulsifying properties, which can be labeled as food or food ingredients and has thickening and emulsifying capabilities. Summary of the Invention
[0005] In order to overcome the shortcomings of the prior art, the present invention provides an emulsified starch and its preparation method, which does not contain any food additives and can be labeled as food or food ingredient, and has the ability to thicken and emulsify.
[0006] The technical solution adopted by this invention to solve its technical problem is: In a first aspect, this application provides a method for preparing emulsified starch, comprising the following steps: Starch is mixed with water to make a starch slurry; After treating the starch milk with α-amylase, it is washed, dried, and crushed to obtain structure-adjusted starch; each gram of starch is treated with 0.5 IU to 5.0 IU of the α-amylase for 2 to 6 hours. The structure-adjusting starch is mixed with oil, wherein the amount of oil is 0.1% to 4.0% of the mass of the structure-adjusting starch, and then heat-treated under shearing and stirring, followed by cooling to obtain the emulsified starch.
[0007] The emulsified starch prepared by the method provided in this application does not require labeling of food additives, has good emulsification stability, and the production process is green and environmentally friendly, requiring no discharge of high-salt wastewater.
[0008] Furthermore, the solid-liquid ratio of the starch milk is 1:1.2~1.6.
[0009] The solid-liquid ratio of starch slurry ensures uniform and controllable enzymatic hydrolysis. If the solid-liquid ratio is too high and the system is too thick, starch granules will be densely packed, resulting in high mass transfer resistance. Amylase will have difficulty spreading evenly to all granule surfaces, which can easily lead to local over-hydrolysis or local under-hydrolysis, resulting in large batch-to-batch differences in the final starch performance. If the solid-liquid ratio is too low and the system is too thin, the amylase molecules will diffuse rapidly, and hydrolysis will be concentrated on the granule surface, making it impossible to form a loose porous structure from the surface to the inside, resulting in insufficient subsequent oil penetration.
[0010] Within this solid-liquid ratio range, the starch slurry maintains a suitable suspension state, starch granules are uniformly dispersed, and amylase can uniformly contact the granule surface. After treatment, each starch granule has a similar oil-binding capacity. After subsequent mixing and heat treatment, the overall product emulsification performance fluctuates little, and batch stability is high. At the same time, this concentration range balances production efficiency and energy consumption. It avoids excessive washing and drying processes due to an overly thin liquid, and also avoids the need for higher-powered stirring equipment to maintain suspension due to an overly thick liquid, thus meeting the cost and efficiency requirements of industrial mass production.
[0011] A suitable solid-liquid ratio is the fundamental prerequisite for achieving controllable enzymatic hydrolysis. It directly determines the interfacial characteristics of starch by structural adjustment, thereby affecting the uniformity and strength of oil-oil complexes, and ultimately impacting the emulsification stability of the finished product.
[0012] Furthermore, the temperature of the heat treatment is 110℃~140℃.
[0013] When the temperature is too low, the starch chain segments have limited mobility, the amorphous regions do not fully expand, and the diffusion rate of oil molecules is slow. Most of them remain on the surface of the particles and cannot penetrate into the internal pores to form stable associations with the starch chains, resulting in low degree of complexation and weak emulsification. However, if the temperature is too high, the oil will oxidize, producing undesirable flavor and color changes.
[0014] Furthermore, the heat treatment time is 2h to 4h.
[0015] If the heat treatment time is too short, the oil does not have enough time to diffuse and penetrate into the pores inside the starch granules. Most of the oil only forms a shallow bond with the surface of the granules, resulting in a weak composite and a decrease in emulsification stability over time. If the heat treatment time is too long, the oil is exposed to a high-temperature environment for an extended period, leading to increased oxidation, higher acid value and peroxide value, and deterioration in product flavor and edibility.
[0016] Furthermore, the cooling step includes: first cooling to below 60°C within 3 to 5 minutes, and then allowing it to cool naturally.
[0017] A two-step cooling method, consisting of rapid initial cooling followed by natural cooling, effectively fixes the starch-oil complex structure formed at high temperatures, maximizing the preservation of the product's emulsifying properties. At the end of the high-temperature heat treatment, the starch chains are in a highly extended state, and the association between oil molecules and starch chains is in dynamic equilibrium. If cooling is carried out slowly at a natural rate, some starch chains will gradually rearrange and regenerate, forming a regular crystalline structure. This will squeeze the already complexed oil molecules out of the crystalline region, causing some oil to revert to a free state, reducing the proportion of effectively complexed oil and consequently decreasing emulsifying stability. Simultaneously, oil molecules will migrate and aggregate during the slow cooling process, forming tiny oil droplets, further weakening the emulsifying effect.
[0018] Rapid cooling first can quickly reduce the mobility of starch chain segments, freezing the stretched conformation at high temperatures. This prevents starch molecules from retrograde and rearranging, and also prevents fat molecules from migrating and aggregating, thus preserving as much of the complex structure formed during the heat treatment stage as possible. Below 60°C, the mobility of starch chain segments is already significantly reduced, and further forced cooling has little marginal gain on conformational fixation. In industrial production, it may even lead to surface condensation and moisture absorption.
[0019] Rapid cooling can be achieved using a double-sided water-cooled jacketed plate or by placing it directly in a cold chamber.
[0020] Furthermore, before the step of mixing the structure-adjusting starch with the oil, a step of rehydration is also included: spreading the structure-adjusting starch evenly and placing it in an environment with a relative humidity of 85%~95% and a temperature of 30℃~40℃ for 15min~30min.
[0021] The rehydration step improves the surface state of structure-adjusting starch, significantly enhancing the penetration depth and binding strength of oils. After drying and crushing, the surface moisture content of structure-adjusting starch granules is low, placing them in a dense, glassy state. When mixed directly with oils at this stage, the oils have difficulty penetrating the interior.
[0022] The rehydration process is carried out under specified temperature and humidity conditions. Water molecules slowly penetrate into the surface of the granules, causing the amorphous areas to absorb moisture and plasticize, while the crystalline areas slightly relax. Micro-cracks appear on the surface, exposing more pores obtained from enzymatic hydrolysis. The granule surface transforms from a rigid glassy state to a flexible rubbery state. Starch granules in this state possess channels for oil penetration while maintaining their overall granule shape, preventing gelatinization and clumping, and significantly increasing the contact area and binding sites between oils and starch chains. However, the temperature, humidity, and duration of the rehydration process must be strictly controlled to avoid overall swelling and gelatinization.
[0023] Furthermore, the step of mixing the structure-adjusting starch with the oil includes: stirring the structure-adjusting starch and the oil at 300 rpm to 500 rpm for 1 min to 3 min, and then increasing the speed to 1800 rpm to 2100 rpm and stirring for 1 min to 2 min.
[0024] After rehydration, the surface of the starch granules becomes flexible and the pores open. Initially, low-speed stirring allows the oil to slowly spread and wet the surface of all starch granules, initially penetrating the surface along the open micro-cracks and pores to form a uniform oil film. Then, increasing the speed further forces the surface oil into the internal pores and subsurface of the granules, while simultaneously breaking up any slight agglomerations, ensuring a uniform oil load on the starch granules.
[0025] Furthermore, prior to the heat treatment, the mixture of the structure-adjusting starch and the oil is dried to a moisture content of 10% to 12%.
[0026] Drying the mixture to a moisture content of 10%~12% before heat treatment can solve the problem of high moisture content caused by rewetting. The rewetting step increases the moisture content of the starch granules. If directly exposed to a high-temperature environment of 110℃~140℃, the moisture inside the granules will rapidly vaporize, forming an outward steam flow that carries unbonded oils to the granule surface. This causes the oils that were originally penetrated into the subsurface layer to be pushed back to the surface, forming free oil droplets. In rare cases, granule adhesion and difficulty in sieving may occur.
[0027] Reducing the moisture content to 10%~12% allows for the removal of most of the free water introduced during rewetting under mild conditions. The starch surface shrinks slightly as it loses water, embedding the absorbed oils within the pores and surface, preventing subsequent oil migration at high temperatures. However, if the moisture content is too low, plasticization is insufficient, restricting starch chain movement and slowing the compounding rate.
[0028] Specifically, a belt dryer or fluidized bed dryer can be used to dry at 65-75°C for 20-40 minutes.
[0029] Furthermore, the starch is selected from at least one of waxy corn starch, tapioca starch, potato starch, corn starch, glutinous rice starch, and wheat starch.
[0030] Waxy corn starch has a very high amylopectin content, resulting in weak gelatinization and high viscosity after gelatinization. After enzymatic hydrolysis and compounding with oils, it forms a tough interfacial film and produces a high-viscosity emulsion system, making it suitable for sauces, thick soups, and other products requiring high viscosity. Tapioca starch has a low gelatinization temperature and high transparency. After compounding with oils, it exhibits a balanced hydrophilic and lipophilic ratio, making it suitable for emulsified beverages requiring high transparency. Potato starch naturally contains phosphate ester groups, making it more hydrophilic. After compounding with oils, it is better suited for oil-in-water emulsion systems, exhibiting excellent emulsion stability. These starches are all conventional food ingredients, require no modification, are widely available, and have controllable costs. They can be directly labeled as food ingredients and do not need to be included in food additive management.
[0031] Secondly, this application provides an emulsified starch, which is prepared by the emulsified starch preparation method described in the first aspect.
[0032] The beneficial effects of this invention are: emulsified starch can be prepared without the addition of food additives, and the resulting product does not need to be labeled with food additives when sold. The production process is green and environmentally friendly, and there is no need to discharge high-salt wastewater. The emulsified starch has good emulsification stability and can be widely used in the food industry. Detailed Implementation
[0033] To make the objectives, technical solutions, and advantages of the embodiments of this disclosure clearer, the technical solutions of the embodiments of this disclosure are described clearly and completely below. Obviously, the described embodiments are only some, not all, of the embodiments of this disclosure. All other embodiments obtained by those skilled in the art based on the described embodiments of this disclosure without creative effort are within the scope of protection of this invention.
[0034] It should be understood that, without conflict, any and all embodiments of the present invention can be combined with technical features of any other embodiment or multiple other embodiments to obtain other embodiments. The present invention includes such combinations to obtain other embodiments.
[0035] Unless otherwise specified, all technical and scientific terms used herein have the standard meaning in the field to which the claimed subject matter pertains. Where multiple definitions exist for a term, the definition herein shall prevail.
[0036] This application provides a method for preparing emulsified starch, including the following steps: Starch is mixed with water to make a starch slurry; Starch milk was treated with α-amylase, washed, dried, and crushed to obtain structure-adjusted starch; 0.5 IU to 5.0 IU of α-amylase was used per gram of starch, and the treatment time was 2 to 6 hours. The structure-adjusted starch is mixed with oil, the amount of oil being 0.1% to 4.0% of the mass of the structure-adjusted starch. The mixture is then heat-treated under shearing and stirring (2400 rpm to 9000 rpm) and cooled to obtain emulsified starch.
[0037] Within the specified enzyme activity and time range, starch is not completely degraded into small molecules. Hydrolysis mainly occurs in the amorphous region of the starch granules, which moderately reduces the degree of polymerization of starch molecules and forms loose micropores and more exposed chain segments inside the granules. After washing and drying to remove soluble oligosaccharides and enzymes, the structurally adjusted starch retains an intact granular skeleton and has a much larger contact interface than the original starch, providing sufficient binding sites for subsequent lipid compounding.
[0038] After mixing with oil, shearing and stirring disperse the oil into tiny droplets, which uniformly adhere to the surface of starch granules and penetrate into the granules through the pores formed by enzymatic hydrolysis. During heat treatment, the mobility of starch chain segments increases with increasing temperature, and the amorphous regions gradually expand, ultimately forming a starch-oil complex with both hydrophilic and lipophilic properties. This complex can form a dense interfacial film at the oil-water interface without the introduction of chemical esterification groups, preventing oil droplet aggregation and achieving a stable emulsification effect.
[0039] The enzymatic hydrolysis modification and oil heat treatment processes are complementary and indispensable. Unhydrolyzed native starch granules have a dense structure, allowing oils to float only on the surface. Even after heat treatment, they cannot form a stable complex structure and have almost no emulsifying ability. Excessive enzymatic hydrolysis leads to excessive starch degradation, a significant decrease in paste viscosity, and loss of thickening effect. This solution controls the degree of enzymatic hydrolysis within a specific range, ensuring sufficient complexation sites and emulsifying activity while preserving the thickening properties of starch. This allows the final product to simultaneously meet the dual requirements of emulsification stability and system thickening. The entire production process does not use chemical modifying agents, produces no high-salt organic wastewater, and the product can be labeled as a food ingredient, avoiding restrictions on food additive use and meeting current clean label market demands.
[0040] The emulsification stability test methods for the examples and comparative examples are as follows: Weigh 6g of emulsified starch (dry basis), add deionized water to a total weight of 200g, gelatinize in a 95℃ water bath for 15min, add water to make up to 200g, cool to 25℃, weigh 100g of the paste and transfer it to a 500mL beaker, add 100g of white oil, and use a high-speed shearing machine to shear and emulsify at 9000rpm for 5min. Transfer 50mL to a centrifuge tube and centrifuge at 2000rpm for 20min. Read the scale value N (mL) of the emulsion phase after centrifugation. Emulsion stability (%) = N / 50*100.
[0041] Emulsification stability ≥80% passed; An emulsification stability of ≤79% is considered a failure.
[0042] Example 1 1000g of waxy corn starch (octane-dry weight) was mixed to prepare a starch slurry at a solid-liquid ratio of 1:1.2. The mixture was pre-treated with α-amylase at a dosage of 0.50 IU of enzyme per gram of starch for 2 hours. After treatment, the starch was washed, dried, and pulverized. 2.0% (by weight of starch) of oil was added, and the mixture was simultaneously heat-treated at 120℃ for 2 hours to obtain the emulsified starch product. The composition and heat treatment process of each sample are shown in the table below.
[0043]
[0044] Untreated waxy corn starch was evaluated as a control in the same manner, and the results are shown in the table below:
[0045] Example 2 1000g of waxy corn starch (octane-dry weight) was mixed to prepare a starch slurry at a solid-liquid ratio of 1:1.5. The mixture was then pre-treated with α-amylase at a dosage of 1.00 IU of enzyme per gram of starch for 4 hours. After treatment, the starch was washed, dried, and pulverized. Oil was added, and the mixture was simultaneously heat-treated at 120℃ for 2 hours to obtain the emulsified starch product. The composition and heat treatment process of each sample are shown in the table below.
[0046]
[0047] The emulsified starch samples 5-20 were tested for emulsification stability, and the results are shown in the table below:
[0048] Example 3 1000g of waxy corn starch (octane-dry weight) was mixed to prepare a starch slurry at a solid-liquid ratio of 1:1.6. The mixture was then pre-treated with α-amylase at a dosage of 5.00 IU of enzyme per gram of starch for 6 hours. After treatment, the starch was washed, dried, and pulverized. 1.0% oil was added, and the mixture was simultaneously heat-treated at high speed to obtain the emulsified starch product. The composition and heat treatment process of each sample are shown in the table below.
[0049]
[0050] The emulsification stability of emulsified starch samples 21-27 was tested, and the results are shown in the table below:
[0051] Example 4 Samples 1-4 were prepared into 25% starch slurries, and then pregelatinized into pregelatinized starches 28-31 using a double-roller pregelatinization apparatus. The emulsion stability was evaluated according to the emulsion stability scheme, and the results are shown in the table below:
[0052] The results above show that the starch treated with oil still retains its emulsifying ability after pregelatinization and can be used as emulsified starch.
[0053] Example 5 1000g of glutinous rice starch (octane-dry weight) was mixed to prepare a starch slurry at a solid-liquid ratio of 1:1.5. The mixture was then pre-treated with α-amylase at a dosage of 2.00 IU of enzyme per gram of starch for 4 hours. After treatment, the starch was washed, dried, and pulverized. Oil was added, and the mixture was simultaneously heat-treated at 120℃ for 2 hours to obtain the emulsified starch product. The composition and heat treatment process of each sample are shown in the table below.
[0054]
[0055] Using untreated glutinous rice starch as a control, its emulsification stability was evaluated, and the results are shown in the table below:
[0056] Comparative Example 1 1000g of waxy corn starch was heat-treated at 120℃ for 2 hours to obtain 40g of finished starch product.
[0057] 1000g of waxy corn starch (octane-dry weight) was mixed with a solid-liquid ratio of 1:1.5 to prepare starch milk. α-Amylase was used for pretreatment at a dosage of 1.00 IU of enzyme per gram of starch for 4 hours. After treatment, the starch was washed, dried, pulverized, and heat-treated at 120℃ for 2 hours to obtain starch product 41.
[0058] 1000g of glutinous rice starch was heat-treated at 120℃ for 2 hours to obtain starch product 42.
[0059] 1000g of glutinous rice starch (dry weight) was mixed with a solid-liquid ratio of 1:1.5 to prepare starch milk. α-Amylase was used for pretreatment at a dosage of 1.00 IU of enzyme per gram of starch for 4 hours. After treatment, the starch was washed, dried, pulverized, and heat-treated at 120℃ for 2 hours to obtain starch product 43.
[0060]
[0061] Example 6 1000g of waxy corn starch (octane-dry weight) was mixed to prepare a starch slurry at a solid-liquid ratio of 1:1.5. The slurry was then pretreated with α-amylase at a dosage of 1.00 IU of enzyme per gram of starch for 4 hours. After treatment, the starch was washed, dried, and pulverized. The powder was placed in a sealed container, and steam was introduced to control the relative humidity at 90% and the temperature at 35℃ for 20 minutes for rehydration. After removal, 1.0% (by weight of starch) of different types of oils were added, and the mixture was high-speed mixed while simultaneously heat-treated at 120℃ for 2 hours to obtain the emulsified starch product. The composition and processing techniques of each sample are shown in the table below.
[0062]
[0063] The emulsification stability of emulsified starch samples 44-47 was tested, and the results are shown in the table below:
[0064] Example 7 1000g of waxy corn starch (octane-dry weight) was mixed to prepare a starch slurry at a solid-liquid ratio of 1:1.5. The slurry was pre-treated with α-amylase at a dosage of 1.00 IU of enzyme per gram of starch for 4 hours. After treatment, the starch was washed, dried, and pulverized. The powder was placed in a sealed container, and steam was introduced to control the relative humidity at 90% and the temperature at 35℃ for 20 minutes for rehydration. Then, 1.0% (by weight of starch) of different types of oils were added. The mixture was first stirred at a low speed of 500 rpm for 2 minutes, then increased to a high speed of 2000 rpm for 2 minutes. After mixing, the mixture was further heat-treated at 120℃ for 2 hours using even higher speed shearing to obtain the emulsified starch product. The composition and processing methods of each sample are shown in the table below.
[0065]
[0066] The emulsification stability of emulsified starch samples 48-51 was tested, and the results are shown in the table below:
[0067] Example 8 1000g of waxy corn starch (octane-dry weight) was mixed to prepare a starch slurry at a solid-liquid ratio of 1:1.5. The slurry was pre-treated with α-amylase at a dosage of 1.00 IU of enzyme per gram of starch for 4 hours. After treatment, the starch was washed, dried, and pulverized. The powder was placed in a sealed container, and steam was introduced to control the relative humidity at 90% and the temperature at 35℃ for 20 minutes for rehydration. Then, 1.0% (by weight of starch) of different types of oils were added. The mixture was first stirred at 500 rpm for 2 minutes, then increased to 2000 rpm for 2 minutes of high-speed shearing. After mixing, the mixture was pre-dried in hot air at 70℃ for 30 minutes to reduce the moisture content to approximately 11%. Subsequently, the mixture was sheared and stirred at high speed, and then heat-treated at 120℃ for 2 hours to obtain the emulsified starch product. The composition and processing methods of each sample are shown in the table below.
[0068]
[0069] The emulsification stability of emulsified starch samples 52-55 was tested, and the results are shown in the table below:
[0070] Example 9 1000g of waxy corn starch (octane-dry weight) was mixed with a solid-liquid ratio of 1:1.5 to prepare a starch slurry. Pretreatment with α-amylase was performed at a dosage of 1.00 IU of enzyme per gram of starch for 4 hours. After treatment, the starch was washed, dried, and pulverized. The powder was placed in a sealed container, and steam was introduced to control the relative humidity at 90% and the temperature at 35℃ for 20 minutes for rehydration. After removal, 1.0% of the starch mass of different types of oils were added. The mixture was first stirred at 500 rpm for 2 minutes, then increased to 2000 rpm for 5 minutes of high-speed shearing. After mixing, the mixture was pre-dried in hot air at 70℃ for 30 minutes to reduce the moisture content to approximately 11%. Subsequently, the mixture was sheared and stirred at high speed, and then heat-treated at 120℃ for 2 hours. After heat treatment, the mixture was immediately transferred to a 0℃ forced cooling air device to cool to 55℃ within 4 minutes, and then allowed to cool naturally to room temperature to obtain the emulsified starch product.
[0071] A control group (samples 60-63) was set up using the same process but with natural cooling to compare the effect of cooling method. The composition and processing of each sample are shown in the table below.
[0072]
[0073] The emulsification stability of emulsified starch samples 56-63 was tested, and the results are shown in the table below:
[0074] Comparing the test results of Examples 2 and 6, it can be seen that under the same enzymatic hydrolysis conditions, oil addition amount, and heat treatment process, adding a rehydration step improved the emulsification stability of the four oil samples by an average of 2.4-2.6 percentage points. Specifically, the olive oil group saw an increase from 92.3% to 94.5%, and the palm oil group from 91.8% to 94.2%. This result verifies that rehydration can cause the starch granules to absorb moisture and plasticize, slightly relax the crystalline region, and generate microcracks and open pores, providing physical penetration channels for the oil and significantly increasing the contact area and binding sites between the oil and starch chains, thereby improving the degree of complexation and emulsification stability.
[0075] Comparing the test results of Examples 6 and 7, it can be seen that the variable-speed mixing process further improves emulsification stability by 0.7 to 0.8 percentage points compared to single high-speed mixing. In the low-speed stage, the oil is evenly spread and wets all particle surfaces, initially penetrating the surface layer along the opened microcracks, avoiding localized oil accumulation. In the high-speed stage, mechanical shearing force is used to squeeze the oil into the microcracks and internal channels of the particle surface, achieving deep wetting.
[0076] Comparing the test results of Examples 7 and 8, it can be seen that adding a low-temperature pre-drying step before heat treatment reduces the material moisture content to 10%~12%, further improving emulsification stability by about 0.6 percentage points. Pre-drying removes excess free water introduced by rewetting, avoiding oil migration caused by the violent vaporization of moisture during high-temperature heat treatment; simultaneously, the starch surface shrinks slightly with water loss, forming a physical interlocking and locking of the oil that has penetrated into the pores, thus increasing the proportion of effective oil actually participating in the compounding. This step not only improves emulsification stability but also reduces the precipitation of free oil in the finished product, improving the product's storage stability and sieve pass rate.
[0077] Comparing the test results of Examples 8 and 9, it can be seen that the two-step cooling process improves emulsification stability by 0.7 to 0.8 percentage points compared to natural cooling. Rapid cooling freezes the starch molecular chain conformation that is in a stretched state under high-temperature heat treatment, inhibiting starch retrogradation and recrystallization during slow cooling, and preventing the already composite oil from being squeezed out by the crystallized areas; at the same time, the viscosity of the oil increases rapidly with the sudden drop in temperature, and there is no time for migration and aggregation, so that the starch-oil composite structure formed at high temperature is completely preserved.
[0078] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, material, or characteristic described in connection with the embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0079] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention.
Claims
1. A method for preparing emulsified starch, characterized in that, Includes the following steps: Starch is mixed with water to make a starch slurry; After treating the starch milk with α-amylase, it is washed, dried, and crushed to obtain structure-adjusted starch; each gram of starch is treated with 0.5 IU to 5.0 IU of the α-amylase for 2 to 6 hours. The structure-adjusting starch is mixed with oil, wherein the amount of oil is 0.1% to 4.0% of the mass of the structure-adjusting starch, and then heat-treated under shearing and stirring, followed by cooling to obtain the emulsified starch.
2. The method for preparing emulsified starch according to claim 1, characterized in that, The solid-liquid ratio of the starch milk is 1:1.2~1.
6.
3. The method for preparing emulsified starch according to claim 1, characterized in that, The heat treatment temperature is 110℃~140℃.
4. The method for preparing emulsified starch according to claim 3, characterized in that, The heat treatment time is 2h to 4h.
5. The method for preparing emulsified starch according to claim 3, characterized in that, The cooling process includes: first cooling the temperature to below 60°C within 3 to 5 minutes, and then allowing it to cool naturally.
6. The method for preparing emulsified starch according to claim 1, characterized in that, Before the step of mixing the structure-adjusting starch with the oil, the step of rehydration is also included: spreading the structure-adjusting starch evenly and placing it in an environment with a relative humidity of 85%~95% and a temperature of 30℃~40℃ for 15min~30min.
7. The method for preparing emulsified starch according to claim 6, characterized in that, The step of mixing the structure-adjusting starch with the oil includes: stirring the structure-adjusting starch and the oil at 300 rpm to 500 rpm for 1 min to 3 min, and then increasing the speed to 1800 rpm to 2100 rpm and stirring for 1 min to 2 min.
8. The method for preparing emulsified starch according to claim 6, characterized in that, Prior to the heat treatment, the mixture of the structure-adjusting starch and the oil is dried to a moisture content of 10% to 12%.
9. The method for preparing emulsified starch according to claim 1, characterized in that, The starch is selected from at least one of waxy corn starch, tapioca starch, potato starch, corn starch, glutinous rice starch, and wheat starch.
10. An emulsified starch, characterized in that, It is prepared by the emulsified starch preparation method according to any one of claims 1 to 9.
